2007
DOI: 10.1002/cncr.22503
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of p53 and pRb expression in superficial bladder cancer patients treated with BCG and interferon‐alpha

Abstract: BACKGROUNDNuclear p53 and retinoblastoma protein (pRb) were reported to be poor prognostic indicators for transitional cell carcinoma of the bladder. The authors sought to determine the prognostic value of nuclear p53 and pRb in superficial bladder transitional cell carcinoma patients who were treated with intravesical bacille Calmette‐Guerin (BCG) or BCG with interferon‐alpha (IFN‐α).METHODSA prospective histological review was performed for 80 superficial bladder transitional cell carcinoma patients who unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 42 publications
5
34
0
Order By: Relevance
“…The clinical relevance of pRb expression in human tumours is still controversial: low levels of this protein have been found to correlate with a worse prognosis in prostate, breast, endometrial, head and neck cancer but not in bladder and gastric cancers [10,19,20,[25][26][27][28]. In these data the loss of pRb protein was observed in 9/67 cases (13.4) and was significantly correlated with T status (p=0.03) and local recurrence (p=0.035).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical relevance of pRb expression in human tumours is still controversial: low levels of this protein have been found to correlate with a worse prognosis in prostate, breast, endometrial, head and neck cancer but not in bladder and gastric cancers [10,19,20,[25][26][27][28]. In these data the loss of pRb protein was observed in 9/67 cases (13.4) and was significantly correlated with T status (p=0.03) and local recurrence (p=0.035).…”
Section: Discussionmentioning
confidence: 99%
“…The CK7 and CK20 antigen staining was recommended for differential diagnostic of low-differentiated carcinomas in order to distinguish their adenomatous versus squamous cell origin (40). The CK7 and p63 antigen staining along with the detection of high molecular cytokeratin (HMWCK/clone 34βE12) were frequently applied to recognize the invasively growing HG UCs in males from their non-differentiated prostatic counterparts (20,31,50).…”
mentioning
confidence: 99%
“…Some investigators reported that P53 and Ki-67 protein overexpression are independent predictors for recurrence in NMIBC treated with BCG [23,24], but others have reported no significant associations [25][26][27][28]. The results for ezrin protein expression were similarly inconsistent [24,27,29].…”
Section: Tumor Markersmentioning
confidence: 99%
“…The results for ezrin protein expression were similarly inconsistent [24,27,29]. Recently, pRb was proposed as a predictive factor of nonresponse and recurrence after BCG plus IFN-α [28]. However, because these markers have not been confirmed by a prospective study, debate about these issues remains.…”
Section: Tumor Markersmentioning
confidence: 99%